Electrodeposition of Compact and Porous Cu-Zn Alloy Electrodes and Their Use in the Cathodic Reduction of Nitrate. Issue 6 (23rd March 2015) - Mattarozzi, Luca; Cattarin, Sandro; Comisso, Nicola; Gerbasi, Rosalba; Guerriero, Paolo; Musiani, Marco; Vázquez-Gómez, Lourdes; Verlato, Enrico
Abstract : Compact and porous Cu-Zn alloys were electrodeposited from citrate baths. The latter deposits, consisting of a spongy material with a macroscopic interconnected porosity (pore diameter of tens of microns), were obtained at large current densities (−3 A cm −2 ) causing strong hydrogen evolution. Porous deposits with compositions between Cu62 Zn38 and Cu91 Zn9 were obtained by varying the ions concentrations in the deposition baths, with optimal morphology for the Cu70 Zn30 composition. The lattice parameter of the samples, estimated from XRD data, showed in the explored range a linear dependence on composition, consistent with formation of a solid solution of Zn in Cu. The alloy materials were tested in nitrate reduction in alkali by voltammetry, chronoamperometry and constant potential electrolysis. Their performances were compared with those of similar (compact and porous) Cu electrodes. The nitrate reduction current decayed rapidly at compact Cu electrodes and was stable at the other electrodes, being the highest at porous Cu70 Zn30 . In all cases, the main product was ammonia.